Isolation and plasmid characterization of carbapenemase (IMP-4) producing Salmonella enterica Typhimurium from cats - Abraham, Sam (Sci Rep, 2016)
Carbapenem-resistant Enterobacteriaceae (CRE) are a pressing public health issue due to limited therapeutic options to treat such infections. CREs have been predominantly isolated from humans and environmental samples and they are rarely reported among companion animals. In this study we report on the isolation and plasmid characterization of carbapenemase (IMP-4) producing Salmonella enterica Typhimurium from a companion animal. Carbapenemase-producing S. enterica Typhimurium carrying bla(IMP-4) was identified from a systemically unwell (index) cat and three additional cats at an animal shelter. All isolates were identical and belonged to ST19. Genome sequencing revealed the acquisition of a multidrug-resistant IncHI2 plasmid (pIMP4-SEM1) that encoded resistance to nine antimicrobial classes including carbapenems and carried the bla(IMP-4)-qacG-aacA4-catB3 cassette array. The plasmid also encoded resistance to arsenic (MIC-150 mM). Comparative analysis revealed that the plasmid pIMP4-SEM1 showed greatest similarity to two bla(IMP-8) carrying IncHI2 plasmids from Enterobacter spp. isolated from humans in China. This is the first report of CRE carrying a bla(IMP-4) gene causing a clinical infection in a companion animal, with presumed nosocomial spread. This study illustrates the broader community risk entailed in escalating CRE transmission within a zoonotic species such as Salmonella, and in a cycle that encompasses humans, animals and the environment.